Characterization of tin-plated steel - Pandey, Shatrudhan; Mishra, Karan Kumar; Ghosh, Pampa; Singh, Abhishek Kumar; Jha, Sanjay Kumar (Frontiers in Materials, 2023)
Tinplating on steel is a useful industrial process extensively used for food packaging. Cold-rolled annealed steel coated with tin gives the steel corrosion resistance property and a beautiful luster. Tinplating on steel is a complex process where rolled and annealed steel sheets are cleaned with acid to remove rust, grease, or oil from the surface. Pure tin is electrodeposited on this freshly prepared surface after the electrodeposition of tin on the steel strip; the surface becomes lustrous, the color of pure tin appears, and the finish is called matte. Very often, the flowing heat treatment is just about the tin melting point of 232°C–265°C. After electrodeposition, pure tin deposits on the steel surface; however, a chemical reaction between tin and iron occurs during the brightening treatment. This process results in iron–tin intermetallic formation; their orientation grain structure and orientation of substrate steel all have a synergistic effect on the final properties of tin-coated steel. In the present study, an attempt has been made to study this parameter in detail. A total of five commercially produced tin-plated steel have been selected for the present purpose, and both tin coating and substrate steel have been thoroughly characterized by optical microscopy, scanning electron microscopy, X-ray diffraction (XRD), and the crystallographic texture point of view; however, the best result has been discussed in this paper. The different phases of tin and the iron–tin compound have been identified using XRD, X-ray, and a texture goniometer that are used to find out the crystallographic texture observed in the presence of FeSn2, FeSn, and Sn in tin coating; the volume fraction of these phases is observed to vary from one sample to another. This variation may affect tinplating steel’s final property, which can be studied in the future work.